Penurunan Tingkat Depresi Pada Lansia dengan Terapi Reminiscence - Sonhaji Sonhaji; Heni Wijayanti; Nurul Ainun Nafisah (JENDELA NURSING JOURNAL, 2021)
Background: increasing age will cause physical and structural changes and a decline in function. The problem of the elderly that often is the lack of ability to adapt to psychological changes so that the elderly will experience psychological disorders, one of which is depression.Purpose: to determine the effect of reminiscence therapy on depression levels in the elderly in Rw 03 Pojok Village, Pulokulon 2 Health Center Working Area, Grobogan Regency.Methods: pre-experimental research with a one-group pre-test and post-test design approach. The sample is 16 respondents. Data analysis in this study was analyzed using paired t-test (Paired t-Test).Results: the level of depression before being given Reminiscence therapy in the elderly showed an average value of 6.25 while the level of depression after being given Reminiscence therapy showed an average value of 2.94 which means it decreased with p_value = 0.000 0.05.Conclusion: there is an effect of reminiscence therapy on decreasing depression levels in the elderly with p_value = 0.000.Suggestion: Provide guidance and direction to the elderly and their families to carry out reminiscance therapy activities to reduce the level of depression in the elderly independently.